Aid and Human Rights: The Case of US Aid to Israel. (1st January 2018) - Ali, Murad
Abstract : The paper examines the allocation of economic as well as military aid from the United States (US) to Israel and investigates whether the US has ever linked its aid to human rights performance in case of the Jewish State. In doing so, the paper explores US foreign aid policies in the light of US Congressional legislation enacted in 1974, which aimed at linking the provision of US aid to human rights performance of aid recipient governments. An assessment of US foreign aid policies illustrates that the US has rarely acted upon such legislation in letter and spirit to terminate or restrict aid to governments involved in violation of the globally recognized human rights. Focusing on US bilateral aid policies during three distinct periods: the Cold War, the post-Cold War and the 'war on terror'; this study shows that instead of linking aid to respect for human rights in the case of Israel, the US has rather authorized more aid to the Jewish State despite the latter's dismal record of human rights performance. The paper illustrates that the provision of US aid is not inspired by the promotion of democracy, liberty and human rights in aid-receiving states. The study concludes that when US foreign policy goals including political, security and geo-strategic interests are at stake, human rights are not significant dynamics behind US aid distribution to Israel or any other US strategic partners.